An economist's guide to the Kalman filter - Venegas, Francisco; De Alba, Enrique; Ordorica, Manuel (Estudios Económicos de El Colegio de México, 1995)
Almost since its appearance, the Kalman Filter (KF) has been successfully used in control engineering. Unfortunately, most of its important results have been published in engineering journals with language, notation and style proper of engineers. In this paper, we want to present the KF in an attractive way to economists by using information theory and Bayesian inference.